2021
DOI: 10.1248/bpb.b21-00163
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-221 Upregulates the Expression of P-gp and Bcl-2 by Activating the Stat3 Pathway to Promote Doxorubicin Resistance in Osteosarcoma Cells

Abstract: microRNA-221 (miRNA-221) is upregulated in several malignant tumors and is associated with poor patient prognosis. Therefore, the present study aimed to investigate the role and underlying mechanism of miRNA-221 in doxorubicin (DOX) resistance in osteosarcoma cells. We constructed DOX-resistant Saos-2/DOX cells and treated them with DOX. Cell viability was determined by performing an MTT assay. Cells were transfected with either miRNA-221 mimic or miRNA-221 inhibitor; real-time quantitative reverse transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…As we all know, miRNA usually exerts its function in repressing gene expression at post-transcription level [ 40 ]. However, other regulatory manners, such as transcriptional regulation via interacting with the promoter or cofactors of transcription factors in the nucleus is also been found [ 41 , 42 ]. Additionally, the different region of miRNA all can be involved in regulating target expression.…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, miRNA usually exerts its function in repressing gene expression at post-transcription level [ 40 ]. However, other regulatory manners, such as transcriptional regulation via interacting with the promoter or cofactors of transcription factors in the nucleus is also been found [ 41 , 42 ]. Additionally, the different region of miRNA all can be involved in regulating target expression.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs, binding to untranslated region located in 3′ tail (3′-UTR) of mRNA, modulate its function through the im- pact on translation process, therefore miRNAs regulate gene expression post-transcriptionally. 33,34) The expression of glycolytic enzyme Hexokinase 2 (HK2) was targeted regulated by miR-143-5p, which has been proved to be downregulated in lung cancer through excessive activation of mammalian target of rapamycin (mTOR) signalling pathway. 35) Similarly, the expression of miR-124-5p in NSCLC cells exerted its cancer suppressor function by decreasing lung cancer cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…P-glycoprotein is a drug efflux pump and its overexpression by tumor cells has been implicated in multidrug resistance in several solid tumors [ 35 ]. In OST, p-glycoprotein has been associated with resistance to chemotherapy and it has been hypothesized that targeted therapy to p-glycoprotein could be of importance to overcome the chemotherapy resistance in OST [ 36 , 37 , 38 ]. When we explored the risk or protective value of the presence of each tumor marker, we observed that patients with p-glycoprotein expression had a higher chance of death occurrence, despite only presenting a statistical value close to the significance level.…”
Section: Discussionmentioning
confidence: 99%